Human Ovarian Follicles Xenografted in Immunoisolating Capsules Survive Long Term Implantation in Mice - Brunette, Margaret A.; Kinnear, Hadrian M.; Hashim, Prianka H.; Flanagan, Colleen L.; Day, James R.; Cascalho, Marilia; Padmanabhan, Vasantha; Shikanov, Ariella (Frontiers in Endocrinology, 2022)
Female pediatric cancer survivors often develop Premature Ovarian Insufficiency (POI) owing to gonadotoxic effects of anticancer treatments. Here we investigate the use of a cell-based therapy consisting of human ovarian cortex encapsulated in a poly-ethylene glycol (PEG)-based hydrogel that replicates the physiological cyclic and pulsatile hormonal patterns of healthy reproductive-aged women. Human ovarian tissue from four donors was analyzed for follicle density, with averages ranging between 360 and 4414 follicles/mm3. Follicles in the encapsulated and implanted cryopreserved human ovarian tissues survived up to three months, with average follicle densities ranging between 2 and 89 follicles/mm3 at retrieval. We conclude that encapsulation of human ovarian cortex in PEG-based hydrogels did not decrease follicle survival after implantation in mice and was similar to non-encapsulated grafts. Furthermore, this approach offers the means to replace the endocrine function of the ovary tissue in patients with POI.